2005
DOI: 10.1080/02615470500050560
|View full text |Cite
|
Sign up to set email alerts
|

Using an Online Support Site to Extend the Learning to a Graduate Field Practicum in the United States

Abstract: An online support site was constructed for graduate social work students at San Diego State University in California during their first-year field practicum. A study was conducted to explore and describe the attitudes of these students toward the usefulness of the site's online features. Students participated in the site through the Blackboard Software Platform by adding discussion threads to asynchronous forums on an online discussion board, receiving information through online announcements, accessing fieldr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The sharing of information through online discussion forums has been a source of support for students involved in practical social work placements (Quinney 2005;Roberts-DeGennaro et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The sharing of information through online discussion forums has been a source of support for students involved in practical social work placements (Quinney 2005;Roberts-DeGennaro et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In an online environment, class information such as announcements and expectations are readily available at all times as opposed to having to take notes in a face-to-face classroom setting. In a study of an online field education support site for social work students in their field practicum, students reported that the most useful feature of the website was the online announcements (Roberts-DeGennaro et al, 2005). In addition, younger, more Social Work Education 763 traditionally aged students, who have come of age surfing the net, may feel more comfortable learning from the web in their natural environment as opposed to sitting still listening to a lecturer for an hour or more (Lam, 2009).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Anecdotally, social work programs in general have historically resisted the online or distance education approach to social work practice courses, reasoning that the skills and techniques central to social work practice can only be adequately addressed in Social Work Education 849 a traditional classroom environment (Roberts-DeGennaro et al, 2005). This resistance is common in academic programs that include vocational skills training such as social work, nursing, and education.…”
Section: Literature Reviewmentioning
confidence: 98%